Causes, frequencies, and predictors of relapse in patients with ulcerative colitis on long-term follow-up in a tertiary care hospital of Northern India - Rahul Jain; Vani Singh; A K Naik; Santosh Kumar Singh; Barun Kumar Chakrabarty; Priya Ranjan; Premshankar Kumar (Journal of Marine Medical Society, 2022)
Context: Ulcerative colitis (UC) initially thought to be a disease of developed world is equally common in India. Surprisingly, there are very scant data from India. The study was undertaken to find the frequency of relapse and to determine factors predictor of relapse in Indian population. Subjects and Methods: This study was conducted at a tertiary care center of New Delhi for a period of 1 year. Patients were included if they had a diagnosis of UC based on accepted historical, endoscopic, histological, and/or radiologic criteria. Detailed past/present history, baseline clinical examination, dietary details, and psychological analysis using shortened Depression Anxiety Stress Scale score, biochemical tests, inflammatory markers, endoscopic, and histopathological analysis were done at baseline and regular intervals. The outcome was clinical relapse or continued remission. Results: Out of 86 patients screened, 50 patients were included in the study according to inclusion criteria and were followed up. The frequency of relapse was 32%. Univariate analysis showed higher relapse frequency, frequency of steroid received in past, patients on immunomodulator therapy, presence of acute or chronic inflammatory cells on histology, and disease activity at baseline as predictors of relapse. There was no significant difference between anxiety, stress, and depression relapsers and those who maintained remission. On multivariate analysis, disease activity at baseline was the only independent predictor of relapse. Conclusions: Stringent control of disease activity with mucosal healing should be the aim, as mucosal healing is the only predictor for prolonged remission.